Multimodal imaging analysis of macular dystrophy in patient with maternally inherited diabetes and deafness (MIDD) with m.3243A>G mutation. (4th May 2021) - Oishi, Noriko; Kubota, Daiki; Nakamoto, Kenji; Takeda, Yukito; Hayashi, Mika; Gocho, Kiyoko; Yamaki, Kunihiko; Igarashi, Tsutomu; Takahashi, Hiroshi; Kameya, Shuhei
ABSTRACT: Purpose : Maternally inherited diabetes and deafness (MIDD) is caused by a heteroplasmic m.3243A>G mutation in the mitochondrial DNA. The main ocular feature in MIDD is macular dystrophy. The purpose of this study was to identify the phenotypical characteristics of a patient with MIDD by multimodal high-resolution imaging analyses. Methods : A detailed history and ophthalmic examination were performed on a 39-year-old patient with MIDD. Multi-modal imaging included fundus photography, fundus autofluorescence imaging, fluorescein angiography, spectral-domain optical coherence tomography, OCT-angiography, and adaptive optics imaging. The PCR-invader and whole exome sequencing (WES) methods were performed on the DNA of the patient. Results : A 39-year-old woman with sensorineural hearing loss, diabetes mellitus presented with atrophic perifoveal changes and MIDD was suspected. The PCR-invader and WES methods showed that the patient had a m.3243A>G mutation in the mitochondrial DNA with 29% and 16.7% of the heteroplasmy in the peripheral blood, respectively. Morphological analyses revealed that the areas of photoreceptor degeneration and chorioretinal atrophy were present mainly in the perifoveal region. Multifocal ERGs showed that the perifoveal responses were reduced. Goldmann visual field was significant for a cecocentral scotoma in the right eye and an enlarged blind spot in the left eye. The central isopter was constricted bilaterally. The results of high-resolution retinal imaging by AO revealed that the densities of the cone photoreceptor were significantly reduced in the fovea where no obvious atrophy of the RPE and choroid was observed. Conclusions : Our findings indicate that WES analysis can be used to detect the m.3243A>G mutation in the mtDNA. The results of multimodal imaging analyses indicated that the primary dysfunction of the photoreceptors in the fovea might precede the dysfunction of the RPE in patient with MIDD.